2021
DOI: 10.3390/ma14185145
|View full text |Cite
|
Sign up to set email alerts
|

Towards Analysis and Optimization for Contact Zone Temperature Changes and Specific Wear Rate of Metal Matrix Composite Materials Produced from Recycled Waste

Abstract: Tribological properties are important to evaluate the in-service conditions of machine elements, especially those which work as tandem parts. Considering their wide range of application areas, metal matrix composites (MMCs) serve as one of the most significant materials equipped with desired mechanical properties such as strength, density, and lightness according to the place of use. Therefore, it is crucial to determine the wear performance of these materials to obtain a longer life and to overcome the possib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 65 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…The large number of pores or the wear characteristics of the composite components affected the change of this curve. Excess pore structures will reduce the contact surface area in the early stages of wear [26,30]. Thus, this will reduce heat transfer at the contact surfaces in the early stages of wear and trigger adhesive wear behavior.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The large number of pores or the wear characteristics of the composite components affected the change of this curve. Excess pore structures will reduce the contact surface area in the early stages of wear [26,30]. Thus, this will reduce heat transfer at the contact surfaces in the early stages of wear and trigger adhesive wear behavior.…”
Section: Resultsmentioning
confidence: 99%
“…In bronze used as a self-lubricating bearing material, different materials have been used as lubricants [22][23][24][25]. Among them, the use of graphite as a reinforcement material resulted in significant improvements in wear properties [4,[26][27][28]. The good distribution of graphite on the wear surface and the effect of reducing the friction coefficient provide advantages.…”
Section: Introductionmentioning
confidence: 99%
“…ANOVA test results show that the p -value of all the parameters considered for this experiment is less than 0.05. This clearly depicts that each parameter has a significant effect on the response characteristics [ 44 , 45 ]. From Table 6 , it is also found that wt.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 Nevertheless, the materials produced using this method do not require surface treatment. [6][7][8] It is generally known that adding graphite, a solid lubricant, to the copper matrix can enhance metals' wear and friction characteristics. 9,10 Venkatesh and Vaddi Seshagiri 11 produced copper matrix composite materials by adding Al 2 O 3 and Gr to copper and investigated its wear and corrosion behavior.…”
Section: Introductionmentioning
confidence: 99%